2011
DOI: 10.1042/bj20102118
|View full text |Cite
|
Sign up to set email alerts
|

N-Docosahexaenoylethanolamide promotes development of hippocampal neurons

Abstract: DHA (docosahexaenoic acid, C22:6,n−3) has been shown to promote neurite growth and synaptogenesis in embryonic hippocampal neurons, supporting the importance of DHA known for hippocampus-related learning and memory function. In the present study, we demonstrate that DHA metabolism to DEA (N-docosahexaenoylethanolamide) is a significant mechanism for hippocampal neuronal development, contributing to synaptic function. We found that a fatty acid amide hydrolase inhibitor URB597 potentiates DHA-induced neurite gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
122
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(124 citation statements)
references
References 36 publications
2
122
0
Order By: Relevance
“…It became apparent by the end of the 1990s that the requirement for DHA probably is the primary reason why -3 fatty acids are essential ( 86 ). This tentative conclusion was supported by subsequent fi ndings indicating that DHA enhances cognition ( 87 ) and synaptic function ( 88 ), and that it is converted to lipid mediators that facilitate the resolution of acute infl ammation ( 89 ), provide neuroprotection ( 90 ), and promote hippocampal development ( 91 ).…”
Section: Essential Fatty Acids In Humanssupporting
confidence: 57%
“…It became apparent by the end of the 1990s that the requirement for DHA probably is the primary reason why -3 fatty acids are essential ( 86 ). This tentative conclusion was supported by subsequent fi ndings indicating that DHA enhances cognition ( 87 ) and synaptic function ( 88 ), and that it is converted to lipid mediators that facilitate the resolution of acute infl ammation ( 89 ), provide neuroprotection ( 90 ), and promote hippocampal development ( 91 ).…”
Section: Essential Fatty Acids In Humanssupporting
confidence: 57%
“…Here, we point out that the period of exposure to n-3 PUFAs might be critical as a previous work showed that DHA-depletion in fetal hippocampi from E2 to E16 resulted in decrease in the number of synapses (Cao et al, 2009). Additionally, experiments performed in vitro on hippocampal neurons in culture showed that application of 1µM of DHA increased significantly the total number of synapses compared to control cultures (Kim et al, 2011). This confirmed previous results from Cao et al showing that 10 days of in vitro supplementation with DHA at 1µM significantly promotes synaptogenesis (Cao et al, 2009).…”
Section: )mentioning
confidence: 81%
“…Current knowledge on the role of DHEA in the central nervous system, especially in the amygdala, is limited. DHEA has been found to promote synaptic development and glutamatergic synaptic activity in hippocampal neurons (Kim et al, 2011a;Kim et al, 2011b). DHEA oxidative metabolism products have also been associated with antiinflammatory and neuroprotective properties (Yang et al, 2011).…”
Section: Discussionmentioning
confidence: 99%